FRI0523 Relationship between Ultrasound-Detected Synovitis, Quality of Life and Work Productivity in Patients with Rheumatoid Arthritis of Working Age. (15th July 2016) - Kosevoi Tichie, A.; Janta, I.; Nieto, J.C.; Valor, L.; Saenz, C.; Serrano, B.; Gonzalez, C.; Lopez, J.; Monteagudo, I.; Carreno, L.; Naredo, E.
Abstract : Background: Rheumatoid arthritis (RA) is a debilitating disease and can affect both quality of life (QOL) and work productivity (WP) [1]. Ultrasound (US) is an important imaging technique increasingly used as a reliable tool in evaluating and monitoring RA patients [2]. US-detected subclinical synovitis (SS) has been detected in patients in clinical remission [3]. Objectives: To investigate the relation between US-detected synovitis, clinically detected synovitis and US-detected SS and QOL and WP. Methods: RA patients, aged between 18 and 59 years, with stable paid employment, were recruited. Clinical aseessment included 42 tender joint count (TJC) and 40 swollen joint count (SJC), Disease Activity Score (DAS) 28 and Health Assessment Questionnaire (HAQ). US assessment included 42 joints. At the joint level subclinical B mode synovitis (SSB) was defined as: absence of tenderness and swelling and presence of B mode score for synovitis ≥1 with or without power Doppler (PD) signal. Subclinical PD synovitis (PSS) was defined as absence of tenderness and swelling and presence of a PD score for synovitis ≥0. Global BM and PD scores for synovitis were assessed using the following scores: TS_B = total score of B-mode synovitis, TS_D = total score of PD synovitis, JS_B = count of joints with B-mode synovitis, JS_D =count of joints with PD synovitis, TSS_B = total score of SSB, TSS_D = total score of PSS, JSS_B = count of joints with SSB, JSS_D = count of joints with PSS. QOL [3] was described using 2 main domains: PCS (physical health) and MCS (mental health). WP was assessd using WPAI (work productivity and activity impairment) questionnaire [4]. Results: 104 patients, with a mean age of 49±8 years and a mean disease duration of 141±103 months were included. At the assessment point, most of the patients had long-standing, low activity disease and a low functional impairment, as assessed by the DAS28-ESR and the HAQ, respectively. With the exception of TSS_B, most of the parameters that significantly correlated with QOL and WP were clinical variables. However, these correlations were weak (r ≤0, 39), being the highest with TJC. Conclusions: Neither clinical and US detected synovitis nor US detected SS showed a consistent relation with QOL and WP in our population of RA patients. TJC seems to be the clinical parameter that better correlates with QOL and WP. References: Chorus AMJ, Miedema HS, Boonen A, van der Linden SJ. Quality of life and work in patients with rheumatoid arthritis and ankylosing spondylitis of working age. Ann Rheum Dis 2003;62:1178–1184 Micu MC, Fodor D. Concepts in monitoring the treatment in rheumatoid arthritis- the role of musculoskeletal ultrasound. Part I: synovitis. Med Ultrason. 2015 Sep;17(3):367–76. Gärtner M, Alasti F, Supp G, Mandl P, Smolen JS, Aletaha D. Persistence of subclinical sonographic joint activity in rheumatoid arthritis in sustained clinical remission. Ann Rheum Dis. 2015 Nov;74(11):2050–3. Reilly MC, Zbrozek AS, Dukes EM. The validity and reproducibility of a work productivity and activity impairment instrument. PharmacoEconomics 1993; 4(5):353–65 Disclosure of Interest: None declared